2016
DOI: 10.1016/j.celrep.2016.08.071
|View full text |Cite
|
Sign up to set email alerts
|

PTBP1 and PTBP2 Repress Nonconserved Cryptic Exons

Abstract: The fidelity of RNA splicing is maintained by a network of factors, but the molecular mechanisms that govern this process have yet to be fully elucidated. We previously found that TDP-43, an RNA-binding protein implicated in neurodegenerative disease, utilizes UG microsatellites to repress nonconserved cryptic exons and prevent their incorporation into mRNA. Here, we report that two well characterized splicing factors, polypyrimidine tract-binding protein 1 (PTBP1) and polypyrimidine tract-binding protein 2 (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 42 publications
3
77
2
Order By: Relevance
“…This result might not be surprising, given that much of the core sequences in the RRMs of Matrin3 and PTBP1 are identical (Matsushima et al 1996). Indeed, previous CLIP and PAR-CLIP analyses for HeLa cells (Xue et al 2009;Ling et al 2016) and our PAR-CLIP analysis for SH-SY5Y cells identified pyrimidine-rich sequences as the binding motifs of PTBP1 and we found that 77% of PTBP1-binding clusters were shared by Matrin3.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This result might not be surprising, given that much of the core sequences in the RRMs of Matrin3 and PTBP1 are identical (Matsushima et al 1996). Indeed, previous CLIP and PAR-CLIP analyses for HeLa cells (Xue et al 2009;Ling et al 2016) and our PAR-CLIP analysis for SH-SY5Y cells identified pyrimidine-rich sequences as the binding motifs of PTBP1 and we found that 77% of PTBP1-binding clusters were shared by Matrin3.…”
Section: Discussionsupporting
confidence: 67%
“…; Ling et al . ) and our PAR‐CLIP analysis for SH‐SY5Y cells identified pyrimidine‐rich sequences as the binding motifs of PTBP1 and we found that 77% of PTBP1‐binding clusters were shared by Matrin3.…”
Section: Discussionmentioning
confidence: 67%
“…When TDP-43 is depleted, nonconserved cryptic exons are spliced into messenger RNA, often introducing frameshifts and/or premature stop codons, promoting nonsense-mediated decay of target RNAs. Coupled with the finding that polypyrimidine track-binding protein 1 (PTBP1) and polypyrimidine track-binding protein 2 (PTBP2) repress cryptic exons by utilizing CU dinucleotide repeat, TDP-43 represents the founding member of this unique class of microsatellite binding cryptic exon repressors [17]. Importantly, TDP-43’s role in repressing nonconserved cryptic exons has been maintained across evolution and nonconserved cryptic exon incorporation was readily observed in postmortem brain tissues from ALS and FTD patients [18], suggesting that this splicing defect is one mechanism underlying TDP-43 proteinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main shift in the splicing outcome ratio often occurs when the repressor for a specific splicing event is removed, as opposed to the removal of the activator, making the repressor, in most cases, the dominant regulator of the splicing event (Coelho et al., ). PTBP1 and PTBP2 belong to the hnRNP protein family that are known to act as repressors of tissue‐specific alternative exons in a wide range of targets (Ling et al., ; Wagner & Garcia‐Blanco, ). PTBP1 binds to pyrimidine tracts, where longer pyrimidine tracts result in stronger binding (Chan & Black, ; Keppetipola et al., , ; Markovtsov et al., ).…”
Section: Discussionmentioning
confidence: 99%